The Multiplier Effect and Dynamic System Modeling For Sustainable Drinking Water Resource Management (Case Study of Perumda Tirta Pakuan, Bogor City) - Hamzah Hamzah; Radjab Tampubolon; Towaf Totok Irawan; Benny Osta Nababan; Rino Indira Gusniawan (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Clean water is an essential basic need for the community, so its management must be carried out sustainably. Purpose: This study aimed to quantify the multiplier effect on economic, social, and environmental aspects of the existence of Perumda Tirta Pakuan Kota Bogor for the period 2025-2029 and project the availability of managed drinking water. Design/methodology/approach: The data used in this study are secondary data from both internal sources at Perumda Tirta Pakuan (annual reports and the company website) and macroeconomic data for the city of Bogor obtained from various sources relevant to the purpose of the study. Data analysis in this study used a systems approach, namely a hard system methodology, namely dynamic systems. The dynamic systems approach was used through the stages of input-output diagrams, causal loop diagrams (CLD), and stock flow diagrams (SFD) using Vensim PLE Version 10.3.2 software. Then the model's prediction results were verified and validated through face validity in two FGDs involving experts and practitioners from drinking water management, resulting in a model that is scientifically accountable and well-tested.Finding/Result: The results of the study show that clean water production capacity remains stable at 2.59 m³ per second, whereas usage increases from 1.86 m³ per second in 2025 to 2.26 m³ per second in 2029. Thus, there is a surplus of 0.33 m³ per second or around 10.4 million m³ per year in 2029, which opens up opportunities to expand customer service coverage. This surplus not only guarantees the availability of clean water for the community, but also strengthens the multiplier effect that drives economic productivity and increases the purchasing power of the people of Bogor City. Conclusion: These findings confirm that dynamic system-based planning is important not only to maintain the continuity of clean water supply, but also to maximize its contribution to comprehensive regional development. Originality/value (State of the art): This study provides an up-to-date review by integrating sustainability analysis (triple bottom line) into a dynamic system model for water utilities. Its originality lies in its ability to measure the indirect impacts (multiplier effects) of clean water services on economic productivity and public purchasing power, which are often overlooked in company performance assessments. The findings regarding surpluses that create opportunities for service expansion are practical contributions that policymakers can directly act upon, specifically in Bogor City and more generally in Indonesia. Keywords: drinking water, dynamic system, perumda tirta pakuan, vensim, water resources